Efforts to Accelerate the Breaking of Soursop (Annona Muricata L.) Seed Dormancy with Different Concentrations of H2SO4 and Giberellin - Sitorus, Efbertias; Panataria, Lince Romauli; Manik, Arni Meilina; Saragih, Meylin Kristina; Simanjuntak, Crystina (Indonesian Journal of Agriculture and Environmental Analytics, 2025)
This study aims to accelerate the dormancy breaking of soursop seeds (Annona muricata L.) with different csoncentrations of H2SO4 and Gibberellin. This study used a Completely Randomized Design (RAL) factorial. This study used two factors. The first factor is the concentration of H2SO4 consisting of 4 levels, namely: A0 = Control (No Treatment), A1 = H2SO4 15% (10 minutes), A2 = H2SO4 30% (10 minutes), and A3 = H2SO4 45% (10 minutes). The second factor is the concentration of Gibberellin (GA3), consisting of 3 levels, namely: G1 = 200 ppm (12 hours), G2 = 300 ppm (12 hours), and G3 = 400 ppm (12 hours)—data analysis was done using variance analysis and Duncan's test. The results showed that the concentration of H2SO4 significantly affected germination power and germination age. Gibberellin concentration had a significant effect on germination power and germination age. The interaction of H2SO4 concentration and Gibberellin concentration had no significant effect on germination power or germination age.